2019
DOI: 10.3390/nu11123071
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective Properties of Human-Enriched Serum Following Polyphenol Extract Absorption: Results from an Exploratory Clinical Trial

Abstract: Polyphenols are widely acknowledged for their health benefits, especially for the prevention of inflammatory and age-related diseases. We previously demonstrated that hydroxytyrosol (HT) and procyanidins (PCy), alone or in combination, drive preventive anti-osteoathritic effects in vivo. However, the lack of sufficient clinical evidences on the relationship between dietary phytochemicals and osteoarthritis remains. In this light, we investigated in humans the potential osteoarticular benefit of a grapeseed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…TNF-α and IL-1β are usually considered to be the two key regulators of pro-inflammatory response, which are involved in promoting inflammation and causing tissue damage ( 56 ). A previous study has demonstrated that olive extracts had anti-IL-1β activity in humans ( 57 ). An in vitro study also found that polyphenol-rich olive extracts decreased the mRNA expression of pro-inflammatory cytokines ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α and IL-1β are usually considered to be the two key regulators of pro-inflammatory response, which are involved in promoting inflammation and causing tissue damage ( 56 ). A previous study has demonstrated that olive extracts had anti-IL-1β activity in humans ( 57 ). An in vitro study also found that polyphenol-rich olive extracts decreased the mRNA expression of pro-inflammatory cytokines ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, we found that: (1) ALE metabolites exert hepatoprotective properties in human hepatocytes by counteracting a fatty acid-induced lipotoxic stress that is commonly observed in hypercholesterolemia [ 9 ] and steatohepatitis [ 10 ]; (2) ALE metabolites limit adipogenic differentiation and hypertrophy, a cellular feature of obesity and metabolic syndrome [ 23 ]; (3) finally, ALE metabolites protect chondrocyte from an IL-1β stimulation that mimics osteo-arthritis inflammatory environment [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three healthy volunteers who fasted for 12 h were given at once 8 g of an artichoke leaf extract (ALE). The dose was set according to validated preclinical and clinical data [ 5 , 11 , 14 , 15 , 16 , 17 ]. The ALE extract was given dissolved in 200 mL of water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2016 study by Mevel et al [ 47 ] which investigated a standardized combination of two extracts from grapeseeds and olive in two post-traumatic OA animal models (PTOA) paved the way for the evaluation of this extract at a clinical level by the same research team [ 48 ]. In the light of the promising preclinical results of the grapeseed and olive extract (OPCO), which has a high content of HT and procyanidins (PCy), the research team attempted illuminate the chemical modifications that polyphenols undergo in the human body and determine whether in vitro results could correlate with an ex vivo model.…”
Section: Preclinical and Clinical Studiesmentioning
confidence: 99%